Service Quality in the Performance of Kejapanan Village Employees District - Novita Dwi Herlina; Lailul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to describe and analyze the performance of employees in the administrative services of Kejapanan Village, Gempol District, Pasuruan Regency and to analyze and describe the inhibiting factors and supporting factors of employee performance in Kejapanan village administration services. The research method used is descriptive research with a qualitative approach. The data collection techniques used were interviews, observation and documentation with one key informant including the Kejapanan Village Secretary and four informants including the Head of Service Section, Head of Planning Affairs, one head of Kejapanan Village RT, and one community leader. The data analysis technique in this research is data collection, data reduction, data presentation and conclusion drawing. The results of this study seen from the service quality indicators of the speed of service are quite good and in terms of politeness and friendliness of employees in providing services is quite good. It can be explained that some of these informants can be seen from several service quality indicators that are only partially fulfilled, that the quality of services in Kejapanan Village, Gempol District is quite good and quite maximal.